The intercultural curriculum and the formal educational system - Fonseca Largo, Carlos (2023)
In this review article, we intend to review two terms that are gaining meaning today: The Intercultural Curriculum and the Formal Educational System. With an interpretive hermeneutical approach, the information was collected with a documentary review. It was confirmed that, on the one hand, the Educational System imposes a Formal Curriculum where the Ideology, Power, Control and Legitimacy of the Hegemonic groups that builds Diversity from the Culture of Race, Ethnicity and Nation is present. On the other hand, there is the Curriculum of Interculturality as a mythical option to achieve Justice, Inclusion and Equality in Education, but it is always controlled and limited by the Institution and the State that does not allow its true operation. Both curricula share many ideologies: of power, of order, of legality and, as we will see throughout the article, they do not present concrete ways of constructing a neutral school. For that, he proposes an emancipating critical Intercultural Curriculum with ontological approaches different from that proposed by the hegemonic curriculum.